"He was, undoubtedly, a wonderful character": Black Teachers' Representations of Nat Turner during Jim Crow. Issue 2 (1st October 2016) - Givens, Jarvis R.
Abstract : This article explores Black teachers' representation of Nat Turner in textbooks published between 1890 and 1922. While conventional readings of Black teachers during Jim Crow present them to be staunch enforcers of the politics of respectability, their representations of Turner disrupt such readings and imply that the racial discourse deployed in their classrooms was more complicated than common narratives suggest. These schoolteachers represented Turner as both an insurrectionist and respectable—characteristics deemed incongruent under traditional reading of the politics of respectability. Black teachers asserted the humanity of Turner to their students and presented him as an inspiring character, even if his violent revolt created dis-ease for White society. This case captures a central dilemma in the socio-historical fabric of Black life—namely, the persistent tension between Black accomodationism and Black Nationalism. More pointedly, while little is known about what happened in the intimate settings of Black teachers' classrooms during the Jim Crow era, these examples present an opportunity to explore some of the socio-political dimensions of their pedagogy.